The Complementarity between Corporate Social Responsibility Disclosure Quality and Corporate Social Responsibility Contracting Intensity - Grabner, Isabella; Renders, Annelies; Yang, Lu (The Accounting Review, 2026)
ABSTRACT Firms are facing increasing pressure to provide information about their Corporate Social Responsibility (CSR) commitment. Firms however differ in the quality of how they communicate CSR-related efforts to stakeholders as well as in the intensity of their CSR contracting. We examine the relationship between CSR disclosures and contracting and argue that the designs of the two practices are complements in signaling a CSR commitment. Using hand-collected data to capture disclosure quality of CSR reports and intensity of CSR contracting (i.e., scope, importance, and degree to which CSR metrics are incorporated) for S&P 500 firms, we show that firms indeed align the design choices of the two practices. In addition, firms using both practices intensively are associated with a stronger CSR commitment and more credible CSR disclosures. Finally, we document that firms that face higher credibility concerns show stronger complementarity between the design of these two practices. Data Availability: All data are available from public sources mentioned in the text. JEL Classifications: M14; M40.